2016
DOI: 10.3892/ol.2016.4828
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profile of saliva and plasma from women with impalpable breast lesions

Abstract: Abstract. The present study evaluated the proteomic profile of saliva and plasma from women with impalpable breast lesions using nano-liquid chromatography-quadrupole-time-of-flight (nLC-Q-TOF) technology. Plasma and saliva from patients with fibroadenoma (n=10), infiltrating ductal carcinoma (n=10) and healthy control groups (n=8) were assessed by combinations of inter/intra-group analyses, revealing significant quantitative and qualitative differences. The major differentially-expressed proteins in the saliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…In this report, serum and salivary proteomes showed changes in bitches with CMT when compared to healthy individuals. Some of the proteins that were modulated in the present study such as S100A4 or haptoglobin were also described in previous studies on canine mammary tumors [27] or human breast cancer [14,15,28,29], while other proteins including immunoglobulin gamma-heavy chains A and D or kallikrein-1 were described here for the first time as CMT-related proteins.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In this report, serum and salivary proteomes showed changes in bitches with CMT when compared to healthy individuals. Some of the proteins that were modulated in the present study such as S100A4 or haptoglobin were also described in previous studies on canine mammary tumors [27] or human breast cancer [14,15,28,29], while other proteins including immunoglobulin gamma-heavy chains A and D or kallikrein-1 were described here for the first time as CMT-related proteins.…”
Section: Discussionsupporting
confidence: 54%
“…In serum, higher levels of histone deacetylase proteins were detected in women with recurrent breast cancer in comparison to non-recurrent cases [13]. In saliva, Delmonico et al [14] identified differences in alpha-2-macroglobulin, ceruplasmin, haptoglobin, hemopexin and vitamin D-binding, among others, in women with impalpable breast cancer in comparison to healthy women; and Giri et al [15] identified 166 proteins with different expression in saliva of women with breast cancer in comparison to healthy controls [15]. In dogs, two studies were reported in which 2-DE gel proteomic analyses of canine mammary tumor tissues were performed.…”
Section: Introductionmentioning
confidence: 96%
“…A study carried out by nano-HPLC-Q-TOF MS investigated the proteome profiles of plasma and saliva of patients with fibroadenoma (n = 10), infiltrating ductal carcinoma (n = 10) and healthy controls (n = 8). The major differentially expressed proteins in the saliva of patients compared with controls were α2-macroglobulin and ceruloplasmin, which should be further validated as potential biomarkers of impalpable breast lesions 30 . A differential proteomic analysis using tandem mass tags technology was performed to characterise potential salivary biomarkers for gastric cancer detection.…”
Section: Human Saliva As Diagnostic Body Fluidmentioning
confidence: 99%
“…The relationship between vitamin D levels and age presented significant association only for the control group (P=0.002). For this reason, according to the ROC plot area (0.778) of the control group, a cut-off value of 45 years old for women was determined, with specificity and sensitivity of 60% and 50%, respectively (Figure 1 flight (nLC-Q-TOF) technology was used, and vitamin D-binding protein was found down expressed in the plasma of cases with benign and malignant breast lesions in comparison with controls´ plasmas (Delmonico et al, 2016). In view of these findings, vitamin D-binding protein should be validated as a putative biomarker in a future study.…”
Section: Discussionmentioning
confidence: 99%